Transition to Campus Life: The Perceptions of Visually Impaired Students towards Librarians' Communication Skills - BAYAT BODAGHI, Nahid; Cheong, Loh Sau; Ngah, Zainab Awang (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2019)
Making the transition to campus life can be reminiscent of the season of adolescence for individuals with special needs. This article investigates the role of academic librarians’ communication skills in relation to the success of the transition programme for visually impaired students (VIPs). Data were collected through interviews and focus groups. Participants consisted of five female and thirteen male students between the ages of 20 and 37. The participants considered librarians’ tone of voice, greetings, and conversation as key factors for a successful transition. They also noted that the main obstacles they faced were the lack of opportunity to interact with librarians and the librarians’ lack of disability awareness and knowledge.